Clinical features, presenting symptoms, and surgical results of congenital cholesteatoma based on Potsic's staging system. (May 2014) - Takagi, Taro; Gyo, Kiyofumi; Hakuba, Nobuhiro; Hyodo, Jun; Hato, Naohito
Abstract Conclusions: Potsic's staging system is a clinically useful procedure for evaluating the extent of congenital cholesteatoma (CC). Objectives: We investigated the clinical features, presenting symptoms, and surgical results of CC according to Potsic's staging system. Methods: A total of 71 patients who had undergone surgery at our hospital were retrospectively analyzed for presenting symptoms, the location of cholesteatoma, and surgical results according to Potsic's staging system. Results: Of the 71 patients, 21 were classified as Potsic stage I, 9 as stage II, 31 as stage III, and 10 as stage IV. More than half of the patients with early-stage CC (stages I and II) were diagnosed asymptomatically by a chance visit to a clinic or on ear screening. Others were diagnosed following a complaint of hearing loss, acute otitis media, or otitis media with effusion. The location of CC varied somewhat by stage. In stage I CC, the most frequent location was behind the anterior-superior quadrant of the tympanic membrane; however, in stage III CC, it was behind the posterior-superior quadrant. All patients were treated surgically. Recurrence was detected in 2 of the 71 patients (2.8%); both had stage II CC. Recurrent lesions were removed during revision surgery.